2005
DOI: 10.1016/j.bcmd.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Low serum transferrin levels in HFE C282Y homozygous subjects are associated with low CD8+ T lymphocyte numbers

Abstract: Hereditary hemochromatosis (HH) is a genetic iron overload disease, in the majority of cases associated with homozygosity for the C282Y mutation of the HFE gene. In spite of this genetic homogeneity, there is a great clinical heterogeneity among HH patients. Low CD8 + lymphocyte numbers have been associated with a more severe expression of iron overload in HH patients, and in experimental models of iron overload. HH patients present low serum transferrin levels. Transferrin is an indispensable resource for lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…It would be of interest to determine whether aplastic anaemia patients show the same high NTBI in relation to low sTfR as in DBA. The decreased transferrin levels in all disease groups, parallels findings in hereditary haemochromatosis (Macedo et al , ). This may exacerbate NTBI levels where a primary mechanism for NTBI generation already exists.…”
Section: Discussionsupporting
confidence: 82%
“…It would be of interest to determine whether aplastic anaemia patients show the same high NTBI in relation to low sTfR as in DBA. The decreased transferrin levels in all disease groups, parallels findings in hereditary haemochromatosis (Macedo et al , ). This may exacerbate NTBI levels where a primary mechanism for NTBI generation already exists.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, under normal conditions, ferritin is present in low concentrations in the extracellular milieu. Plasma concentrations of ferritin are only 1.5–30 ng/ ml, compared with 200–320 µg/ml for transferrin [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Macedo et al. [22] reported low CD8 lymphocyte numbers and low serum transferrin levels associated with a more severe expression of iron overload in HH patients. From our limited data it appeared that infectious complications were more common in patients who did not have venesection therapy before LT.…”
Section: Discussionmentioning
confidence: 99%
“…These include an abnormal CD4:CD8 ratio, decreased cutaneous hypersensitivity and abnormal proliferative responses by peripheral blood mononuclear cells to mitogenic stimuli [13,21]. Macedo et al [22] reported low CD8 lymphocyte numbers and low serum transferrin levels associated with a more severe expression of iron overload in HH patients. From our limited data it appeared that infectious complications were more common in patients who did not have venesection therapy before LT.…”
Section: Discussionmentioning
confidence: 99%